In the morphological term (the load on the counterpart) (Journal of the College of Basic Education, 2022)
The use of the term by grammarians reflects the criterion for the rules of their ideas because it is related to reasoning and directing judgments in a sound direction. Like the predicate and the counterpart, they are signs and issues that reflect an important rule of analogy based on analysis and linking between the elements of the predicate and the transcribed, and then they are provisions that grammarians followed when they set the rules.